Synthesis, Characterization and Study of The Liquid Crystalline Behavior of Four and Six Heterocyclic Compounds - Karam, Nisreen Hussein; Tomi, Ivan Hmeed Rouel; Tomma , Jumbad Hermiz (Iraqi Journal of Science, 2022)
The new compounds synthesized by sequence reactions starting from a reaction of 4-hydroxybenzaldehyde with 1,5-dibromo pentane to produce dialdehyde)I(.Then compound )I( reacted with different aromatic amines to give schiff bases )II-IV(,thereafter added acetyl chloride to schiff bases to yield N-acyl derivatives)V-VII(.While1,3-diazetine derivatives)VIII-X( were synthesized from the reaction of N-acyl derivatives with sodium azide.The reaction of thiourea with N-acyl compounds led to formation of thiourea derivatives (XI-XIII).Finally, the pyrimidine compounds )XIV-XVI( were synthesized by ring closure reaction of compounds(XI-XIII) with diethyl malonate.The synthesized compounds were characterized by measurements of melting points,FTIR,1H-NMR and mass spectroscopy for some prepared compounds.The liquid crystalline properties were studied by hot stage polarizing microscopy and differential scanning calorimetry DSC for compound (IX). The compounds)VI(, (IX),(XII) and (XV) display enantiotropic nematic mesophase, while other compounds(V),(VII),( VIII),(X),(XI),(XIII),(XIV) and( XVI) did not show any liquid crystalline properties.